Linguistics of Generative Transformation in Arabic in the Modern Era - Ardia Pramesti Regita Cahyani (An Nazhair: Journal of Arabic Education, 2024)
This research explains the application of generative transformation theory in modern linguistic contexts, especially in Arabic. The method used is a qualitative method with a descriptive approach, and this study highlights the concept of Noam Chomsky's theory, which divides language into external and internal structures, as well as competence and performance. This theory is not only relevant in analyzing the structure of language in the abstract, but also supports a deep understanding of the dynamics of changing the meaning of a language. Factors that affect the change in meaning include socio-cultural development, technological advancement, differences in fields of use and differences intergenerational. The Research shows that this theory is significant in improving the effectiveness of Arabic language learning, especially in compiling a structured linguistic-based curriculum and utilizing modern technology. Through this approach, the challenges of learning Arabic in the digital era can be overcome with more relevant innovations, opening up new opportunities for the development of interactive and student-based learning methods.